Degenerative joint changes of the thoracic spine with respect to sex and age - Bagwell, K. Lauren (2022)
The thoracic spine manifests degenerative changes from aging, obesity, repetitive strain and occupational stress, although sex differences are poorly understood. In this work we examine whether differences in the expression of thoracic degenerative joint changes can be found in females and males with respect to age. The two age groups included in the study are older adults between 50 and 55 years and elderly individuals between 70-75 years from the William M. Bass osteological collection of the University of Tennessee, Knoxville (USA). The first interval represents the onset of skeletal decline. The second is correlated with reduced mobility and an increase in arthritic pain. The thoracic vertebrae from 99 individuals (52 females and 47 males) were macroscopically examined on superior and inferior centra and zygapophyses for lipping, porosity and eburnation following Buikstra and Ubelaker’s (1994) scoring system. Elderly females and males exhibit a higher severity of degenerative changes than older adults, and in males the degree of lipping was extreme. Regarding older adults, males present a greater severity of lipping, extent of lipping, porosity, and extent of porosity than females. However, females show a greater degree of eburnation among older adults, particularly in the lower thoracic vertebrae. When elderly adults are compared, males express a higher degree of lipping, extent of lipping and extent of porosity than females. Like their older adult counterparts, elderly females show evidence of a greater severity in eburnation than males, suggesting hormonal profile disruption associated with reproductive cessation as well as occupational stress, may also cause the deterioration of the intervertebral discs, particularly in the lower thoracic skeleton.